'My land is worth a million dollars': How Japanese Canadians contested their dispossession in the 1940s. (11th August 2017) - Stanger-Ross, Jordan; Blomley, Nicholas
Abstract : On July 31, 1944, Rikizo Yoneyama, a former resident of Haney, British Columbia, an agricultural area east of Vancouver, wrote to the Canadian Minister of Justice to protest the sale of his property. Two years earlier, when he and his family had packed their belongings for their forced expulsion from coastal British Columbia, they could take with them only what they could carry and, like other displaced people, they left much behind. "I realize that we are the victims of a war emergency and as such are quite willing to undergo … hardship … to help safeguard the shores of our homeland, " wrote Yoneyama, "however, I do urgently desire to return to my home … when the present emergency ends. May I plead your assistance in the sincere request for the return of that home?" When letters like his did receive a response from the federal government (there is no record that he did so in this case) it came in the form of standard letter, acknowledging that "the disposal of … property will be a matter of personal concern" but informing Japanese Canadians that, in conformity with a new federal law, everything, including their homes, would be sold.